Penerapan Model Pemebalajaran Berbasis (Problem Based Learning) Pada Keterampilan Menulis Teks Eksplanasi Berbantuan Audio Visual Pada Siswa Kelas X - Muhammad Dzaki Nashrulloh; Diena San Fauziy (Lembaga Pengembangan Kinerja Dosen, 2024)
Since the national curriculum was changed to text-based, explanatory texts have become one of the types of texts that are taught to students in class X of high school. One of the competencies that must be achieved by students in learning explanatory texts is producing. Students are required to be able to produce explanatory texts properly and correctly. However, there are still several problems in the achievement of these competencies. Based on the problems encountered in the field, it is known that innovative and creative explanatory text writing learning media is still lacking. An explanatory text is a text that provides information about a process resulting from the phenomenon of tang occurring. PBL (Problem based Learning) is a method of student-centered learning in this model is to improve students' ability to solve problems, use thinking skills and develop life skills such as critical thinking and teamwork. This mix method was chosen because it has suitability because in this study what is to be answered includes outcomes and the process of developing qualitative and quantitative data because in this method it is more about asking how the needs of high school class X students for the PBL model with learning media to produce explanatory texts based on digital media and local wisdom in order to facilitate and understand the mistakes of the research. In this case, it can also improve students' ability to solve problems, use various thinking skills and develop life skills.